2019
DOI: 10.2174/1871520619666190206165215
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Induced Upregulation of miR-548as-3p Increases Invasion of NSCLC by Targeting PTEN

Abstract: Background: Non-Small Cell Lung Cancer (NSCLC) is an aggressive cancer type due to high metastatic capacity. Nuclear Factor Kappa B (NF-κB) is a consistently active transcription factor in malignant lung cancer cells and has crucial significance in NSCLC progression. It is also implicated in the transcriptional regulation of many genes including microRNAs (miRNAs) that function as tumor suppressor or oncogene. It has been increasingly reported that several miRNAs defined as gene members are induced by NF-κB. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…PTEN is essential for the maintenance of normal cells and acts as a tumor suppressor in human cancers ( 31 ). A large number of studies have reported that PTEN played important roles in tumor development and progression, including lung cancer, ovarian cancer, and prostate cancer ( 23 , 32 , 33 ). Furthermore, in the RB development, PTEN showed an inhibitory effect and it served as the target of multiple miRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTEN is essential for the maintenance of normal cells and acts as a tumor suppressor in human cancers ( 31 ). A large number of studies have reported that PTEN played important roles in tumor development and progression, including lung cancer, ovarian cancer, and prostate cancer ( 23 , 32 , 33 ). Furthermore, in the RB development, PTEN showed an inhibitory effect and it served as the target of multiple miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-296/PTEN axis facilitated gastric cancer tumorigenesis in vitro and in vivo ( 22 ). miR-548 promoted NSCLC cell invasion by regulating PTEN ( 23 ). Moreover, miR-182 promoted breast cancer cell viability and invasion via targeting PTEN ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant miRNAs expression can also be regulated by NF‐κB. The expression of miR‐31‐5p, miR‐146a, and miR‐548as‐3p can be upregulated by NF‐κB, whereas miR‐195 and miR‐497 are negatively regulated with NF‐κB . It has been reported that miR‐19a promotes colitis‐associated colorectal cancer by regulating tumor necrosis factor α‐induced protein 3‐NF‐κB feedback loops and microRNA‐19a promotes cell viability and migration of chondrocytes via upregulation of SOX9 through the NF‐κB pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that PTEN hampers invasion and metastasis of gastric cancer cells through the inhibition of the PI3K/NFkB pathway and preventing the DNA binding of NFkB on the FAK promoter (Zhang et al, 2014). Moreover, PTEN inhibits metastasis in breast cancer cells through the downregulation of WNT1 inducible signaling pathway protein 1 (WISP1) and lipocalin-2 (LCN2) (Chiang et al, 2016), and inactivation of NFkB signaling in non-small cell lung cancer cells (Akgun et al, 2019). A previous study showed that TNFα increased the expression of PTEN through activation of NFkB signaling in HL60 human leukemic cells (Lee et al, 2007).…”
Section: Analysis Of Genetic Alterations Of the Pbmentioning
confidence: 99%